2018
DOI: 10.3324/haematol.2018.200121
|View full text |Cite
|
Sign up to set email alerts
|

Related peripheral blood stem cell donors experience more severe symptoms and less complete recovery at one year compared to unrelated donors

Abstract: Unlike unrelated donor registries, transplant centers lack uniform approaches to related donor assessment and deferral. To test whether related donors are at increased risk for donation-related toxicities, we conducted a prospective observational trial of 11,942 related and unrelated donors aged 18–60 years. Bone marrow (BM) was collected at 37 transplant and 78 National Marrow Donor Program centers, and peripheral blood stem cells (PBSC) were collected at 42 transplant and 87 unrelated donor centers in North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…We sequenced 46 genes mutated recurrently in CH and myeloid malignancies (Data Supplement). 5,6,[19][20][21] We included samples with average unique molecular identifierdeduplicated consensus coverage of at least 1,0003 and considered all variants with a variant allele fraction (VAF) $ 0.005. We classified variants as pathogenic on the basis of published genetic criteria.…”
Section: Genetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We sequenced 46 genes mutated recurrently in CH and myeloid malignancies (Data Supplement). 5,6,[19][20][21] We included samples with average unique molecular identifierdeduplicated consensus coverage of at least 1,0003 and considered all variants with a variant allele fraction (VAF) $ 0.005. We classified variants as pathogenic on the basis of published genetic criteria.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…Although HLA-matched adult donors can be identified in the NMDP registry for 75% of White patients, far fewer patients of color will find matched donors (16%-19% of African Americans, 33%-42% of Asian Americans, and 34%-40% of Hispanic Americans). 5 The best available graft for many patients may thus be from an older donor such as an HLA-identical sibling or haploidentical relative, 6 , 7 highlighting the importance of understanding characteristics of older donors that influence recipient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also found that 35.1% of donors reported disruption to their daily lives due to physical discomfort. Some donors experienced pain up to one year after donation [17]. Healthcare providers should conduct risk assessments of the donors to identify high-risk donors who require special follow-up monitoring or self-management [14].…”
Section: Discussionmentioning
confidence: 99%
“…For other patients, the only available option is an unrelated HLA-matched donor that can be identified through volunteers [ 5 ]. Michael et al’s study (2019) showed that related PBSC donors are at increased risk for donation-related toxicities compared with unrelated donors one year after donation [ 6 ]. However, the likelihood of finding such donors is low because of insufficient or nonexistent national donor programmes in many developing countries [ 7 ].…”
Section: Introductionmentioning
confidence: 99%